A Switching Law to Stabilize an Unstable Switched Linear System (Journal of Nonlinear Modeling and Analysis, 2024)
Stabilization of switched systems fully composed of unstable modesis of theoretical and practical significance. In this paper, we obtain somesufficient algebraic conditions for stabilizing switched linear systems with allunstable subsystems based on the theory of spherical covering and crystal pointgroups. Under the proposed algebraic conditions switching laws are easy to bedesigned to stabilize the switched systems. Some simple examples are providedto illustrate our results.